The Impact of Brand Romance Dimensions on Brand Loyalty: A Study on Uniqlo Indonesia - Febe Surya Effendi; Windy Freshia Luhana; Adelina Proboyo (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2023)
The significant growth of the fashion industry has made it an appealing sector to explore. This research aims to investigate how brand pleasure, brand arousal, and brand dominance influence brand loyalty in UNIQLO Indonesia. The study employed a quantitative approach using a survey method with 75 respondents. The research data was collected through online questionnaires and analyzed using multiple linear regression with SPSS software. The findings indicate that brand pleasure, brand arousal, and brand dominance have a positive relationship with brand loyalty. Furthermore, brand pleasure has the most significant impact on brand loyalty, while brand dominance has the least impact among the three dimensions in affecting brand loyalty in the case of UNIQLO Indonesia.